How resilient are farming households, communities, men and women to a changing climate in Africa? - Pérez, Carlos; Jones, E.; Kristjanson, Patricia M.; Cramer, Laura K.; Thornton, Philip K.; Förch, Wiebke; Barahona, Carlos (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Using a 9-country dataset from sub-Saharan Africa, and integrating quantitative household-level analyses with qualitative work, the paper shows that gender relations affect agricultural practices and adaptation. The women farmers in our sample control less land than men, the land they control is often of poorer quality, and their tenure is insecure. Women, more than men, are dependent on internal village groups, as opposed to organizations operating at regional or national levels. Hence, women have less access to extension and input services, and are less likely than men to use improved seeds, fertilizers, and pesticides. The adaptive capacity of individuals and communities depends on their differential access to resources, economic assets and social capital, which are mediated by their socially defined rights and responsibilities. Highlights include: